Konstruksi Makna Media Massa: Telaah Presentasi Kepemimpinan melalui Semiologi Charles Sanders Peirce - Intan Nurhalima; Dedi Kurnia Syah Putra (Postgraduate of Jayabaya University, 2016)
Film as a medium of mass communication succeeds in forming public percep tions through the construction of reality, build various phenomena through signs and structures of meaning. Film Jodhaa-Akbar is onof those films that one part of it tells of the power of an empire that had triumphed. The phenome non of leadership is always interesting when a source in contact with the study of politics and power issues. Through semiology Charles Peirce, this research study seeks to build leadership through the presentation of a film. Peirce di rects the concept of semiotics toward pragmatism. This research method using a qualitative approach. The studyfowzd that thi:'Ye is a scene that clearly shozus the shape of act s of leadership, such as decision-making illvolving many advi sors among lenders, employee error executing a personal palace, to the totality ( (the Sultan of developing education.